Menggagas Tafsir Harmonis di Indonesia: Reinterpretasi QS. Ali Imran [3]: 110 dalam Perspektif Psikologi - Ulya Fikriyati (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
As a majority group in Indonesia’s plural society, Moslem groups have great potential role as agents of peace and security. It doesn’t mean to castrate the active role of other religions followers, but each group has equal responsibilities and obligations in maintaining the integrity of the Indonesian nation in different way. This article seeks to offer a reinterpretation of the “khayr ummah” verse contained in the QS. Āli 'Imrān [3]: 110. The selection of this verse was based on the possibility of conflict that grows from a less precise understanding of the verse in plural society interactions. To interpret the verse, the author uses a psychological approach using five dangerous ideas as the theoretical framework. Reinterpretation of selected verses is expected to provide new insight and perspective in addressing the label “khayr ummah” that was pinned on Muslims wisely and proportionately.